The Evaluation of Molecular Genetics and Clinical Manifestations in Patients With LZTR1 ‐Associated Noonan Syndrome: A Retrospective Chart Review and Review of Literature - Hager Jaouadi; Şakir Hicazi; Carolyn R. Raski; Lindsey Aschbacher‐Smith; Ghada Hijazi; Amy E. Roberts; Carlos E. Prada; K. Nicole Weaver (American Journal of Medical Genetics Part A, 2026)
ABSTRACT Pathogenic variants in LZTR1 are an established cause of Noonan syndrome (NS) and uniquely exhibit both autosomal dominant (AD) and autosomal recessive (AR) inheritance. However, the phenotypic spectrum and genotype–phenotype correlations remain incompletely defined. We conducted a multi‐center retrospective chart review of patients diagnosed with LZTR1 ‐NS evaluated at three tertiary care centers. Clinical, molecular, and imaging data were systematically collected. A comprehensive literature review (2015–2025) identified 100 additional individuals meeting inclusion criteria. Comparative analyses were performed to evaluate phenotypic patterns by inheritance. Among 21 previously unreported patients aged 6 months to 49 years, 15 had AD NS and 6 had AR NS. Clinical features were largely consistent with prior reports, including high prevalence of craniofacial dysmorphism, neurodevelopmental and multisystem involvement. Cardiac manifestations were frequent, with pulmonary valve stenosis as the most common lesion. Hypertrophic cardiomyopathy appeared more prominent among AR NS. Notably, lymphatic abnormalities were observed at a higher frequency than previously reported. Compared to the literature, our cohort highlights novel findings, including the co‐occurrence of AD LZTR1 ‐NS with 22q11.2 deletion and two patients with AR NS with features suggestive of schwannomatosis. These findings expand the clinical spectrum of LZTR1 ‐NS and have important implications for diagnosis, surveillance, and genetic counseling.